المشكلات النفسية في تعليم مهارة الكلام عند طلاب مدرسة ابن حجر المتوسطة الإسلامية - Setiawan, Arif; Husniyah, Farihatul (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2019)
The increasing number of students in Islamic School  is a new challenge for Arabic teachers in teaching. Problems that may arise in the learning process can be understood, anticipated, and sought solutions to achieve the goal of learning Arabic. There are many aspects that can be seen in the problem of learning Arabic, there are aspects of language, sociolinguistic aspects, psychological aspects and so on. The psychological aspects of learning attitudes have an important role to play in learning success and achievement. Psychological problems that occur in classrooms affect teachers and students. Lack of confidence, speaking anxiety, and low self-esteem make students seem reluctant and do not want to talk or just say simple sentences as exemplified in learning time. The student's attitude seemed to lose confidence in himself, thinking that his friends did not pay attention, were afraid of making mistakes, and so on. While the success of speaking skills in Arabic can only be mastered by the practice of speaking in the classroom.